POLITIK HUKUM DALAM PENGANGKATAN TENAGA HONORER MENJADI PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Anggi Jukrianto; Dodi Haryono; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Very high unemployment rates can cause disruption to security stability.One of the government's actions to reduce unemployment is to open job opportunitiesthrough the procurement of the state civil apparatus. Another problem that arises inaddition to the high unemployment rate is the presence of honorary workers who aremushrooming in various government agencies. The attention of the government is eagerlyawaited and is expected to be able to change their status more clearly and definitely,namely being appointed as civil servants. Law No. 5 of 2014 may also be considered agovernment action aimed at breaking the deadlock on handling unemployment and a wayout for the appointment of honorary workers to be part of civil servants. The purpose ofwriting this thesis, namely; first to find out how legal politics in appointing honoraryworkers to become government employees with work agreements based on Law Number 5of 2014 concerning civil servants. Second to find out how the Regulations for theImplementation of the Appointment of Honorary Personnel to PPPK are conformidablebased on Legal Politics. This type of research can be classified as normative legalresearch, because in this study using literature materials as the main data to analyzecases, and the author did not conduct field research. Data sources used, primary data,secondary data, and tertiary data. The collection technique uses a literature study oflegal materials.From the results of the study there are two main things that can beconcluded. First, There is legal politics in the appointment of honorary workers to PPPKbased on Law No. 5 of 2014 to overcome unemployment problems and provide legalcertainty for honorary workers to be appointed as PPPK. The appointment of honorarystaff is carried out through the stages of planning, announcement of vacancies,applications, selection, announcement of selection results, and appointment to honorarystaff and honorary staff can be appointed as PPPK candidates if they have met therequirements specified in the law. With this mechanism, it is expected that the quality ofservices provided by employees working in government agencies will be better and moreprofessional. Second, The regulations for the appointment of honorary personnel toPPPK are not fully in accordance with the legal politics above. This can be seen from thedetermination of PPPK needs that are not in accordance with the number of honorarypersonnel and various selections made that have not been able to help provide legalcertainty for honorary personnel to become part of ASN. Even honorary personnel whodo not pass the open selection process, then these honorary personnel will lose their jobs.Keywords: Legal Politics-Honorary Workers-Government Employees with WorkAgreements (PPPK)